Estimation of genetic trend for the backfat depth of pigs of Large White breed in two Ukrainian pedigree farm - Getya, Andriy; Nagy, István; Berezovskyy, Nikolay; Kodak, Oleksandr; Farkas, János; Szabó, Csaba (Acta Agraria Kaposváriensis, 2010)
The BLUP method is presently the most widely accepted method for predicting the genetic merit of pigs. However Ukraine is still among the countries where this selection method is awaiting for introduction. Therefore, our aim was to demonstrate the effectiveness of BLUP and REML methods on two selected pedigree farm data near Poltava. Analyses were carried out altogether on 1153 records (167 sires, 549 dams). Backfat measurements were recorded by Piglog 105 instrument over the6/7 thoracic vertebra at the age of 6âˆ’7 months between 1997 and 2007. Due to the very small data size, the genetic parameters of the backfat depth were estimated for the Hungarian Large White dataset. Then with the help of these parameters, breeding values were estimated for the population of the present study using the PEST software applying single trait animal model. Least square means were highly stable for the examined period. Although the effect of year was significant (P<0.01) the differences between the various years proved to be different only between 1994 and 1998 and between 1994 and 1999. Moreover the difference between the largest and smallest least square mean was less than 1 mm. Although the differences in the BLUE estimates were exceeding that of the GLM procedure (Figure 1) still it can be stated that the effects of the year-birth is relatively small, especially during the last 5 years. When the mean breeding values were regressed on the successive years the estimated annual genetic trend was 0.002 mm but it was not significant (P=0.15). This result is unfavourable and suggests that the selection method used in the farms tested is inefficient in respect of backfat thickness.